Detection of axillary lymph node metastasis in breast cancer using dual-layer spectral computed tomography - Li, Huijun; Wang, Huan; Chen, Fangfang; Gao, Lei; Zhou, Yurong; Zhou, Zhou; Huang, Jinbai; Xu, Liying (Frontiers in Oncology, 2022)
Purpose: To investigate the value of contrast enhanced dual-layer spectral computed tomography (DLCT) in the detection of axillary lymph node (ALN) metastasis in breast cancer. Materials and Methods: In this prospective study, 31 females with breast cancer performed contrast enhanced DLCT from August 2019 to June 2020. All the ALNs were confirmed by postoperative histology. Spectral quantitative parameters including λHU (in Hounsfield units per kiloelectron-volt), nIC (normalized iodine concentration), and Zeff (Z-effective value) in both arterial and delay phases were calculated and contrasted between metastatic and non-metastatic ALNs using the McNemar test. Discriminating performance from metastatic and non-metastatic ALNs were analyzed using receiver operating characteristic curves. Results: A total of 132 ALNs (52 metastatic and 80 nonmetastatic ALNs) were matched successfully between surgical label and preoperative label on DLCT images. All spectral quantitative parameters (λHu, nIC, and Zeff) derived from both arterial and delayed phases were greater in metastatic ALNs than in nonmetastatic SLNs (all ps < 0.001). Logistic regression analyses showed that λHu in delayed phase was the best single parameter for the detection of metastatic ALNs on a per-lymph node basis, with area under curve of 0.93, accuracy of 86.4% (114/132), sensitivity of 92.4% (48/52), and specificity of 87.9% (70/80). Conclusion: The spectral quantitative parameters derived from contrast enhanced DLCT, such as the λHu, could be applied for preoperative detection of ALN metastasis in breast cancer.